Entrepreneurial Traits in Recognizing Opportunities By SMES - Jowita TRZCIELINSKA (Communications of International Proceedings, 2021)
The purpose of the paper is to examine what entrepreneurial traits, if any, are essential for opportunity recognition and how intensive they have to present to be statistically significant. Also, our interest is if the same traits refer to both small and medium sized enterprises.To give answers for this research questions we investigated 107 enterprises operating in Poland, including 62 small and 45 medium firms. The results show that small and medium-sized enterprises are not monolithic group and that there are more traits which can be effectively used in medium than in small firms. We have also shown that by looking for the relationship between entrepreneurial traits and opportunity recognition, opportunities can be represented by their symptoms, i.e. the actions of the firm that can be considered as undertaken to seize the opportunity.
Keywords: Entrepreneurial traits; SMEs; Opportunity recognition; Agility.